2013
DOI: 10.1038/cddis.2013.404
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 controls lysosomal acid lipase in adipocytes: implication of lipophagy during nutrient restriction and metformin treatment

Abstract: Finding new molecular pathways and strategies modulating lipolysis in adipocytes is an attractive goal of the current research. Indeed, it is becoming clear that several human age-related pathologies are caused by adipose tissue expansion and altered lipid metabolism. In the present work, we show that transcription factor forkhead homeobox type protein O1 (FoxO1) is upregulated by nutrient restriction (NR) in adipocytes and exerts the transcriptional control of lipid catabolism via the induction of lysosomal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 50 publications
1
76
0
Order By: Relevance
“…These studies highlight distinct roles of TFE3 in differentially regulating lipid metabolism between the liver and adipose tissue. Activation of the transcription factor forkhead box O1 (FOXO1) through nutrient depletion has been shown to induce lipophagy and LAL in adipocytes [81]. Moreover, FOXO1/3/4 liver-specific knockout mice develop hepatic steatosis and hypertriglyceridemia with decreased autophagic flux, which can be reversed upon overexpression of the autophagy gene ATG14 [82].…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…These studies highlight distinct roles of TFE3 in differentially regulating lipid metabolism between the liver and adipose tissue. Activation of the transcription factor forkhead box O1 (FOXO1) through nutrient depletion has been shown to induce lipophagy and LAL in adipocytes [81]. Moreover, FOXO1/3/4 liver-specific knockout mice develop hepatic steatosis and hypertriglyceridemia with decreased autophagic flux, which can be reversed upon overexpression of the autophagy gene ATG14 [82].…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…The net implication of this study was that autophagosomes were capable of selectively sequestering lipid droplets for delivery to lysosomes for lipolysis in fibroblasts and hepatocytes. This process was named ‘Lipophagy’ and has subsequently been characterized in dozens of settings, including neurons [11], macrophages [12], and adipocytes [13]. Subsequent studies have also emphasized that lipophagy is not only important for triglyceride metabolism but also cholesterol catabolism and efflux in cell types such as macrophages [14].…”
Section: Lipophagy – the Bridge Linking Autophagy And Intracellular Lmentioning
confidence: 99%
“…Last, the forkhead box-O (FOXO) family of transcription factors has classically been linked to regulation of autophagy via control of autophagy gene expression. Lettieri Barbato et al [13] found that metformin, an AMPK-activating drug, and nutrient restriction drive FOXO1 mediated increases in lipophagy and lysosomal acid lipase expression in adipocytes. Similarly, FOXO is a major regulator of autophagy genes notably including ATG14 in liver.…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…Mitochondrial membranes have also been suggested as a source for autophagosome membrane lipids, particularly as the mitochondria are the key site for synthesis of phosphatidylethanolamine needed for lipidation of LC3 [110, 111]. During mitophagy, most of the membrane lipids are degraded in the lysosome, liberating free fatty acids [112]; this process may be disrupted in the presence of lipid peroxides, leading to accumulation of lipofuscin [113]. …”
Section: Introductionmentioning
confidence: 99%